Ultrasonic wave propagation in concentrated emulsions and encapsulated emulsions - Chen, Yinghui (2007)
Ultrasonic spectrometry has potential for monitoring chemical processes on line; an important application is the detection of the suspended particle size distribution (PSD) in emulsions. Measured ultrasonic wave attenuation as a function of frequency is compared to the predictions of an adaptive wave propagation model to obtain an estimate of the PSD. Current models are based either on scattering physics, heat transfer, or hydrodynamics, or on a combination of these. Most models give good prediction of attenuation for dilute and semi-dilute systems, but they are known to break down at high dispersed phase concentrations and for very small (10s of nm) particles. The limits of applicability are not known in a formal sense.